Paradigmatic Properties of Noun Unities with the General Meaning of "Courage" in Uzbek - Karimova Hurriyat (International Journal on Integrated Education, 2022)
In this article, the paradigmatic features of lexemes with the word "Courage" are divided into two aspects, i.e. thematic and semantic. Courage is important because the similarities and differences of noun units with a common theme are studied on the basis of the table.